Feedback que funciona : como construir e passar sua mensagem - Weitzel, Sloan R. (Guias de ideias transformadas em ação., 2017)
Providing feedback to others about their performance is a key developmental experience. But not all feedback is effective in making the best use of that experience. This guidebook demonstrates the foundation for effective feedback practice, walking the reader through, step by step and in detail, the feedback method used at CCL. For anyone who wants to get better at giving feedback to anyone, whether they be a peer, direct report, or boss, this guidebook demonstrates how to create an effective message with real impact.